Pregnant maternal brain dorsal anterior cingulate cortex choline/creatine ratios on 1H-MR spectroscopy in opioid exposure - Class, Jonathan A.; Vishnubhotla, Ramana V.; Zhao, Yi; Ooms, Nathan; Haas, David M.; Sadhasivam, Senthilkumar; Radhakrishnan, Rupa (Frontiers in Neuroscience, 2025)
There is growing interest in understanding the effects of opioid use on the brain, yet the effects of opioid use on the pregnant maternal brain are still relatively unknown. Pregnant women with opioid exposure during pregnancy are at high risk for adverse neurological and neuropsychiatric outcomes. Much of what is currently known about the impact of opioids on the maternal brain is mainly derived from studies in animal models; however, species-specific opioid pathways and other socio-environmental factors complicate the interpretation of results. A few studies in non-pregnant adults have shown the utility of magnetic resonance spectroscopy (MRS) in risk prediction in substance exposure. We know that pregnancy alters the pharmacodynamics and pharmacokinetics of opioid metabolism, and the impact of opioids on synapses may differ during pregnancy compared to the non-pregnant state. We, therefore, aimed to understand the neurometabolic alterations in pregnant women on medications for opioid use disorder (MOUD). In our multicenter study, we utilized 1H MRS to analyze metabolic alterations in the dorsal anterior cingulate cortex (dACC) in pregnant women on MOUD (12 subjects) vs. pregnant control women (21 subjects) without substance exposure. Using multivariable linear regression, we identified a positive association between opioid exposure and choline-to-creatine (Cho/Cr) ratios after correcting for gestational age and scanner site. We also identified a significant elevation in the Cho/Cr ratio in pregnant women on MOUD and concomitant polysubstance exposure when compared to pregnant women on MOUD without exposure to other substances and control pregnant women. These altered metabolite concentrations that we identified in the dACC may provide a mechanistic understanding of the neurobiology of MOUD and insights for better management and outcomes.